A Self‐Powered Ethanol Biosensor. Issue 4 (27th January 2017) - Ruff, Adrian; Pinyou, Piyanut; Nolten, Melinda; Conzuelo, Felipe; Schuhmann, Wolfgang
Abstract: We describe the fabrication of a self‐powered ethanol biosensor comprising a β‐NAD + ‐dependent alcohol dehydrogenase (ADH) bioanode and a bienzymatic alcohol oxidase (AOx) and horseradish peroxidase (HRP) biocathode. β‐NAD + is regenerated by means of a specifically designed phenothiazine dye (i. e. toluidine blue, TB) modified redox polymer in which TB was covalently anchored to a hexanoic acid tethered poly(4‐vinylpyridine) backbone. The redox polymer acts as an immobilization matrix for ADH. Using a carefully chosen anchoring strategy through the formation of amide bonds, the potential of the TB‐based mediator is shifted to more positive potentials, thus preventing undesired O2 reduction. To counterbalance the rather high potential of the TB‐modified polymer, and thus the bioanode, a high‐potential AOx/HRP‐based biocathode is suggested. HRP is immobilized in a direct‐electron‐transfer regime on screen‐printed graphite electrodes functionalized with multi‐walled carbon nanotubes. The nanostructured cathode ensures the wiring of the iron‐oxo complex within oxidized HRP, and thus a high potential for the reduction of H2 O2 of about +550 mV versus Ag/AgCl/3 M KCl. The proposed biofuel cell exhibits an open‐circuit voltage (OCV) of approximately 660 mV and was used as self‐powered device for the determination of the ethanol content in liquor. Abstract : Self–powered ! An ethanol biosensor based on a biofuel cell comprised of an ADH/redox‐polymer bioanode and an AOx/HRP biocathode is developed and used for the determination of ethanol in liquor. The ethanol‐powered biofuel cell acts as a self‐powered device, and is thus capable of determining the ethanol content without any applied external voltage. The novel concept may pave the way to miniaturized in vivo ethanol sensors.